Case Report: A rare complication of non-hypertensive HELLP syndrome—microangiopathic coagulation activation leading to postpartum DIC with acute kidney injury - Li, Chunping; Zhang, Jianping; Tang, Yong (Frontiers in Medicine, 2025)
Thrombotic disseminated intravascular coagulation (DIC) associated with hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome in the absence of typical hypertension is rare, and its pathogenesis differs significantly from that of hemorrhagic DIC. Although the overall incidence is low, disease progression is often rapid and carries a high risk of multi-organ failure. Pregnancy-specific physiologic changes, including endothelial injury, hypercoagulability, and a predisposition to microcirculatory thrombosis, markedly increase the likelihood of microangiopathic coagulation activation in non-hypertensive HELLP patients. Therefore, prompt recognition of coagulation abnormalities and timely, targeted interventions are crucial for improving patient outcomes. Here, we report a case of HELLP syndrome without prenatal hypertension that rapidly progressed to DIC and acute kidney injury (AKI), despite only moderate blood loss (800 mL). This case highlights potential mechanisms underlying microangiopathic coagulation activation and provides an important reference for the clinical recognition and management of such occult coagulopathies.